A hypervariable immunoglobulin superfamily member from Crassostrea gigas functions as pattern recognition receptor with opsonic activity. (September 2018) - Liu, Dongyang; Yi, Qilin; Wu, Yichen; Lu, Guangxia; Gong, Changhao; Song, Xiaorui; Sun, Jiejie; Qu, Chen; Liu, Conghui; Wang, Lingling; Song, Linsheng
Abstract: Immunoglobulin superfamily (IgSF), an extensive collection of proteins possessing at least one immunoglobulin-like (Ig-like) domain, performs a wide range of functions in recognition, binding or adhesion process of cells. In the present study, a cysteine-rich motif associated immunoglobulin domain containing protein (designated Cg CAICP-1) was identified in Pacific oyster Crassostrea gigas . The deduced protein sequence of Cg CAICP-1 contained 534 amino acidresidues, with three Ig domains which were designated as IG1, IG2 and IG3, and a cysteine-rich motif between the first and second Ig domain. The mRNA transcripts of Cg CAICP-1 were highly expressed in hemocytes and up-regulated significantly ( p < 0.05) after the stimulation of lipopolysaccharides (LPS), but not peptidoglycan (PGN). The recombinant Cg CAICP-1 protein (r Cg CAICP-1) exhibited binding activity to various pathogen-associated molecular patterns (PAMPs) including LPS, PGN, mannose (Man) and D-galactose (D-Gal), and microorganisms including Vibrio splendidus, Escherichia coli, Staphylococcus aureus, Micrococcus luteus and Pichia pastoris . The phagocytic rates of oyster hemocytes towards Gram-negative bacteria V. splendidus and Gram-positive bacteria M. luteus were significantly enhanced ( p < 0.05) after pre-incubation of microbes with r Cg CAICP-1. Furthermore, the transcripts of Cg CAICP-1 exhibited high level of polymorphism among individuals. The ratio of nonsynonymous and synonymous distances (dN/dS) for AA'BCC'D strands of IG1 (the possible binding sites 1, pbs1) across all allelic variants was 2.09 ( p < 0.05), while the ratio for the non-pbs regions was less than 1.0. The 1248 bp fragment amplified from the 5′ end of Cg CAICP-1 open reading frame (ORF) from 24 transcript variants could be divided artificially into seven regions of 50 elements, and all of the allelic variants might be derived from these elements by point mutation and recombination processes. These results collectively suggested that Cg CAICP-1 might function as an important pattern recognition receptor (PRR) to recognize various PAMPs and facilitated the phagocytosis of oyster hemocytes towards both Gram-positive and Gram-negative bacteria. Diverse isoforms of Cg CAICP-1 were generated through point mutation and recombination processes and maintained by balancing selection, which would provide a broader spectrum of interaction surface and be associated with immune resistance of oysters to infectious pathogens. Highlights: Cg CAICP-1 was a novel member of IgSF identified from oyster Crassostrea gigas. The dimer and monomer forms of Cg CAICP-1 distributed in hemocytes and plasma. Cg CAICP-1 mRNA expression was significantly up-regulated post LPS stimulation. r Cg CAICP-1 exhibited binding activity towards different microbes and opsonin activity. Point mutation and recombination contributed to the Cg CAICP-1 polymorphism.